2016
DOI: 10.1021/acs.orglett.6b02041
|View full text |Cite
|
Sign up to set email alerts
|

Triacetonide of Glucoheptonic Acid in the Scalable Syntheses of d-Gulose, 6-Deoxy-d-gulose, l-Glucose, 6-Deoxy-l-glucose, and Related Sugars

Abstract: Ease of separation of petrol-soluble acetonides derived from the triacetonide of methyl glucoheptonate allows scalable syntheses of rare sugars containing the l-gluco or d-gulo structural motif with any oxidation level at the C6 or C1 position of the hexose, usually without chromatography: meso-d-glycero-d-guloheptitol available in two steps is an ideal entry point for the study of the biotechnological production of heptoses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…In 2016, Liu et al reported a multigram synthesis of L‐glucose from sodium D‐glucoheptonate 16 [27] . Sodium glucoheptanoate can be prepared via well‐known Killiani reaction using sodium cyanide and D‐glucose.…”
Section: Strategies For the Synthesis Of L‐sugarsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2016, Liu et al reported a multigram synthesis of L‐glucose from sodium D‐glucoheptonate 16 [27] . Sodium glucoheptanoate can be prepared via well‐known Killiani reaction using sodium cyanide and D‐glucose.…”
Section: Strategies For the Synthesis Of L‐sugarsmentioning
confidence: 99%
“…In 2016, Liu et al reported a multigram synthesis of Lglucose from sodium D-glucoheptonate 16. [27] Sodium glucoheptanoate can be prepared via well-known Killiani reaction using sodium cyanide and D-glucose. The work portrays the synthesis of a common intermediate 17 that gives access to Lglucose, L-glucoronic acid and L-glucitol (Scheme 3).…”
Section: Head To Tail Inversion Of D-hexosesmentioning
confidence: 99%
“…As previously described, 12 the stable triflate 16, formed in 95% yield from 6, with sodium azide in DMF at -40 °C formed the kinetic glucono-azide 8 (75%) but at room temperature gave the thermodynamic mannonoazide 9 (85%); the initially formed 8 was equilibrated to the more stable all cis-azide 9. For the synthesis of the idono-and gulono-azides 10 and 11, the starting material 6-deoxy-Dgulonolactone 18 was prepared from the triacetonide 17 in 61% yield with no chromatography required; the route 13 is far more convenient than procedures from L-rhamnose 12 or Dgulonolactone (Scheme 3). 14 Reaction of 18 with benzaldehyde in the presence of concentrated hydrochloric acid gave the crystalline lactone 7 (92%) in which the methyl group is equatorial.…”
Section: Synthesis Of Azidolactones 8 9 10 and 11mentioning
confidence: 99%
“…Recently, Fleet, Yoshihara and coworkers (Liu et al, 2016 ) offered a very robust approach to some of the discussed compounds. The synthesis starts with easily available glucoheptanoic acid 19 ( Figure 7 ) with all the OH groups protected as acetonides.…”
Section: Bifunctional Monomers Equipped With Additional Reactive Moiementioning
confidence: 99%